T-cell receptor repertoires as potential diagnostic markers for patients with COVID-19. (December 2021) - Hou, Xianliang; Wang, Guangyu; Fan, Wentao; Chen, Xiaoyan; Mo, Chune; Wang, Yongsi; Gong, Weiwei; Wen, Xuyan; Chen, Hui; He, Dan; Mo, Lijun; Jiang, Shaofeng; et al.
Highlights: Decreased TCR repertoire diversity and longer CDR3 length were found in COVID-19 patients. TRBV/J gene usage and overlap indices are abnormal in COVID-19 patients. CDR3 length and recombination events are abnormal in COVID-19 patients. Disease-associated TCRβ clones are useful in the diagnosis of COVID-19. Abstract: Objective: Coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), is an ongoing global health emergency. T-cell receptors (TCRs) are crucial mediators of antiviral adaptive immunity. This study sought to comprehensively characterize the TCR repertoire changes in patients with COVID-19. Methods: A large sample size multi-center randomized controlled trial was implemented to study the features of the TCR repertoire and identify COVID-19 disease-related TCR sequences. Results: It was found that some T-cell receptor beta chain (TCRβ) features differed markedly between COVID-19 patients and healthy controls, including decreased repertoire diversity, longer complementarity-determining region 3 (CDR3) length, skewed utilization of the TCRβ variable gene/joining gene (TRBV/J), and a high degree of TCRβ sharing in COVID-19 patients. Moreover, this analysis showed that TCR repertoire diversity declines with aging, which may be a cause of the higher infection and mortality rates in elderly patients. Importantly, a set of TCRβ clones that can distinguish COVID-19 patients from healthy controls with high accuracy was identified. Notably, this diagnostic model demonstrates 100% specificity and 82.68% sensitivity at 0–3 days post diagnosis. Conclusions: This study lays the foundation for immunodiagnosis and the development of medicines and vaccines for COVID-19 patients.